Waterborne polyurethane modified with silicone macromer and the nylon airbag coated with it. Issue 19 (November 2016) - Go, Cheol Wan; Yang, Jeong Han; Kwak, Dong-sup; Kim, Gi-Woong; Jeong, Han Mo
A waterborne polyurethane (WPU) with a double bond in the main chain was modified with a poly(dimethylsiloxane) (PDMS) macromer having a terminal methacrylate group (PDMS methacrylate macromer) by using a radical mechanism, and the changes in various physical properties were examined. Although the crystallinity of the soft segment domain increased, the cohesion of the hard segments was weakened as a result of the modification with the PDMS methacrylate macromer. The adhesion between the WPU and nylon decreased due to the hydrophobic/low polarity of the PDMS component, and this improved the flexibility and the tear strength of the nylon-6, 6 textile coated with WPU. The air permeability of the coated textile also increased as a result of the modification.